If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + x) = 0 (5 * 3 + x * 3) = 0 (15 + 3x) = 0 Solving 15 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 3x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 3x = 0 + -15 3x = 0 + -15 Combine like terms: 0 + -15 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 4(9c-1)-2=34c+4 | | -3y-11=6y+52 | | 7x-5-2x=x+8+x | | 2f-4=2f+4 | | -9c+1=-44 | | 2t-3=3(t+7) | | 4(y-3)=y-12 | | -14x-20=-13x+50 | | 3-(1-y)=3+5y | | 8x-4=9x+8 | | 12(3x-5)=3(12x+6) | | 4(1x+4)=28 | | 17x+13x=180 | | y+23y+2.9=5(y+6.7) | | .62+.42=x | | x^2-4x=17 | | 17x+13x= | | 7x+7=-4+5x+19 | | 7(-3x+1)=20(x+1) | | -3x+10=34 | | -(v+2)=3+v | | x+76=228 | | x+3x=580 | | 5+2w=88 | | x+x= | | x+0.125=-0.75 | | 2(b+2)-(5+b)=-3 | | 2m+7n=10 | | 2(2w+5-w)=88 | | .42*7= | | 0.363636363636x=20 | | -3(4y-5)-y=-2(y-2) |